EuReCa_Serbia 2014-2023. ANALYSIS OF THE RESUSCITATION ATTEMPS BEFORE, DURING, AND AFTER THE COVID-19 PANDEMIC - Lazić, Aleksandra (Journal Resuscitatio Balcanica, 2025)
Introduction: EuReCa Serbia study collects data on out-of-hospital cardiac arrest (OHCA) from October 1, 2014, including the period during the coronavirus disease 19 (COVID-19) pandemic. The aim of this paper is to analyze the data on OHCA and its outcomes and compare them between the periods before, during and after the period of the COVID-19 pandemic.Material and Methods: The study included epidemiological data on OHCA collected through the EuReCa study questionnaire during the period 2014-2023. Data on OHCA incidence,frequency of initiation/non-initiation of cardiopulmonary resuscitation (CPR), participation of bystanders in applying CPR, as well as the incidence of shockable initial heart rhythm, return of spontaneous circulation on scene (any ROSC), admission to hospital with spontaneous circulation,were collected and their association and trend before, during and after the COVID-19 pandemic in Serbia were analyzed.Results: During the COVID-19 pandemic period, the annual incidence of recorded OHCA cases was 49.23/100,000 inhabitants compared to 114.78/100,000 before and 105.52/100,000 after the pandemic. The incidence of CPR initiation per 100,000 inhabitants in the same time periods was significantly different and amounted to 34.95 before, 48.14 during, and 75.20 after the pandemic.In percentage terms,decrease in the frequency of bystander CPR was observed during the pandemic period (10.03%), compared to the period preceding it (13.13%), while an significant increase was observed after the pandemic period (19.56%),but a trend of increasing incidence of bystander CPR per 100,000 inhabitants was observed before, during and after the pandemic periodcontinuously (4.59; 4.83 and 14.71 respectively).A significantly reduced incidence of ROSC during the COVID-19 pandemic of 15.21% was observed compared to 21.55% and 31.11% before and after the pandemic, respectively. The annual incidence of survival to hospital admission per 100,000 inhabitants among the groups of OHCA cases before, during, and after the pandemic was also significantly different among these periods (6.12, 6.54, and 16.21, respectively). Conclusion: The EuReCa_Serbia registry observed a decrease in the incidence of OHCA during the COVID-19 pandemic, compared to the periods before and after the pandemic. The incidence of bystander CPR had an increasing trend looking before, during, and after the pandemic. The incidence of any ROSC, hospital admission with spontaneous circulation was unchanged before and during, while an increase was observed in the post-pandemic period.
Keywords: Out-of-hospital cardiac arrest, COVID-19 pandemic, cardiopulmonary resuscitation, ROSC